Prevalence of lactose intolerance among children with severe acute malnutrition with diarrhea admitted to the Institute of Child and Mother Health, Bangladesh - Adnan, Mohammad Ahad; Rahman, Md. Abdur; Hossain, Belal; Ali, Hossain; Bhuiyan, Amjad Shaker; Hye, Abdul (World Nutrition, 2025)
BackgroundLactose intolerance (LI) is a common complication of severe acute malnutrition (SAM). However, in low-income countries it is often not possible to determine whether LI is present.ObjectiveThis study aimed to document the prevalence of LI among SAM cases with diarrhea admitted to the Institute of Child and Mother Health, Bangladesh.MethodsThis cross-sectional study was carried out from July 2022 to June 2023 in all admitted children aged 2 months to 59 months diagnosed as SAM with diarrhea either at presentation or during the disease course. Children having invasive diarrhea, cystic fibrosis, celiac disease, inborn error of metabolism and associated serious comorbidity were excluded, leaving a sample size of 61. Stool reducing substance ≥1+ by Benedict test and stool PH < 5.5 by pH strip were considered to be a positive test for LI.ResultsThe prevalence of LI in our sample was 28%. The predominant age group was 6-23 months (48%); 48% resided in a peri-urban area. Consumption of animal as well as formula milk was a common practice in all age groups. Kwashiorkor (46%) was the commonest malnutrition type with 39% LI association. LI was significantly associated with persistent diarrhea. These patients had a longer hospital stay as well. On logistic analysis, the presence of perianal excoriation, a history of diarrhea in the 2 months prior to hospitalization, and heavy stool frequency in the last 24 hours were found to be significant predictors for LI.ConclusionsThe prevalence of LI in SAM patients was 28%. Persistent diarrhea, the presence of perianal excoriation, diarrhea in the last 2 months, and heavy stool frequency in the last 24 hours were significantly associated with LI.